2022
DOI: 10.1007/s00432-022-03990-7
|View full text |Cite
|
Sign up to set email alerts
|

Early stage breast cancer follow-up in real-world clinical practice: the added value of cell free circulating tumor DNA

Abstract: Purpose Physical examinations and annual mammography (minimal follow-up) are as effective as laboratory/imaging tests (intensive follow-up) in detecting breast cancer (BC) recurrence. This statement is now challenged by the availability of new diagnostic tools for asymptomatic cases. Herein, we analyzed current practices and circulating tumor DNA (ctDNA) in monitoring high-risk BC patients treated with curative intent in a comprehensive cancer center. Patients and metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 35 publications
(39 reference statements)
0
2
0
Order By: Relevance
“…They found that in nearly all evaluated cases (with the exception of a few cases involving bone or liver metastases), ctDNA became detectable before any signs of disease spread. Moreover, the average time from ctDNA detection to the identification of suspicious findings on follow-up imaging was approximately 3.81 months, with a mean time to a definitive recurrence diagnosis of 8 months ( 116 ). Similarly, another study involving serial ctDNA testing in patients with early-stage breast cancer who had undergone neoadjuvant chemotherapy (post/preoperative) showed that the detection of ctDNA during follow-up was strongly associated with disease recurrence.…”
Section: Ctdna and Breast Cancer Follow-upmentioning
confidence: 99%
“…They found that in nearly all evaluated cases (with the exception of a few cases involving bone or liver metastases), ctDNA became detectable before any signs of disease spread. Moreover, the average time from ctDNA detection to the identification of suspicious findings on follow-up imaging was approximately 3.81 months, with a mean time to a definitive recurrence diagnosis of 8 months ( 116 ). Similarly, another study involving serial ctDNA testing in patients with early-stage breast cancer who had undergone neoadjuvant chemotherapy (post/preoperative) showed that the detection of ctDNA during follow-up was strongly associated with disease recurrence.…”
Section: Ctdna and Breast Cancer Follow-upmentioning
confidence: 99%
“…In the sensitivity analysis, the resulting trends remained the same as those in the above analysis after removing the five low-quality comparisons, as shown in Figure S1. 15,18,21,24,32 (HR: 5.42, 95% CI: 3.34-8.75, p < 0.001, I 2 = 51%) The NOS scores of 23 included literatures ranged from 5 to 9. Funnel plots were chosen to estimate publication bias in this study and no obvious bias was observed.…”
Section: Sensitivity Analysis and Publication Biasmentioning
confidence: 99%